Evaluating the Correlation Between Stress or Phobia Due to Dental Procedure and Level of Saliva Secretion - Jamdar, Dr Sami Faisal; Alshammari, Dr Ahmed; Almutairi, Dr Manal Mohammad; Albandar, Dr Malak; Asiri, Dr Saja Abdulaziz; Hussain, Dr Abdullah Al; Alshammari, Dr Majid (International Journal of Innovative Research in Medical Science, 2022)
Aim: This study focuses on evaluating the correlation between stress or phobia due to dental procedure and level of saliva secretion among the patients coming for dental treatment. Materials and Methods: 200 medically healthy patients who required local anaesthesia for dental procedures were included. Sample collection was done at three different stages of treatment. In stage1, samples were collected after the patient had just entered the clinic and were discussing his problem sitting in normal chair in front of the Dentist. After the patients were seated in dental chair, before administering anaesthesia, samples were collected in stage 2 and in stage 3, immediately after administering local anaesthesia. One single spit of patient was collected at every stage in sterile container and measured with calibrated pipette. Results: As documented in many studies the patient undergoing dental treatment experiences maximum stress before getting the local anaesthesia. Our study revealed that in stage 2 when patient was about to undergo Local anaesthesia, saliva secretion was at minimum level averaging at 0.2 ml (ranging from 0 to 0.4). Saliva secretion was maximum in stage 1, when the patient was comfortably sitting in normal chair discussing their dental issues. In stage 3 the saliva secretion slightly improved compared to stage 2 as after the anaesthesia the anxiety level of the patient started to diminish. Conclusion: This study suggests that there is clinical correlation between stress levels and the amount of saliva secretion. Excessive stress can even lead to xerostomia as experienced by some patients.